2022
DOI: 10.1155/2022/8257256
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Posterior Maxillary Arch for Orthodontic Miniscrew Insertion Using Cone Beam Computed Tomography: A Cross-Sectional Analysis

Abstract: Background and Aim. The aim of this study is to assess the cortical bone thickness and interradicular distance between posterior maxillary teeth using cone beam computed tomography (CBCT). Methods and Materials. Cone beam computed tomography records of 35 patients (70 quadrants) from maxilla were evaluated. The images were analyzed using the NNT viewer software (version 23). The measurements were made on axial sections at 2, 4, 6, and 8 mm from CEJ. The optimal sites were defined in terms of mesiodistal palata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A length of 6.0 mm seemed to be preferable to avoid a collision against the tooth roots. Previous studies have reported that the interradicular distance was 2.4-6.5 mm in the maxillary palatal region and 2.4-3.3 mm in the buccal region [15,16]. As the diameter of miniscrews is usually about 1.5 mm, an error at the bottom of the hole of more than 0.5 mm might be critical.…”
Section: Discussionmentioning
confidence: 97%
“…A length of 6.0 mm seemed to be preferable to avoid a collision against the tooth roots. Previous studies have reported that the interradicular distance was 2.4-6.5 mm in the maxillary palatal region and 2.4-3.3 mm in the buccal region [15,16]. As the diameter of miniscrews is usually about 1.5 mm, an error at the bottom of the hole of more than 0.5 mm might be critical.…”
Section: Discussionmentioning
confidence: 97%
“…These concerns are consistent with recommendations from Smith and coworkers, who stressed the want for customized plans to maximize implant stability and minimize risks. 16…”
Section: Implications For Miniscrew Implant Placementmentioning
confidence: 99%